Mapping, temporal dynamics, and assessment of agricultural ecosystem services: evidence from eastern India - Rath, Suvangi; Das, Amarendra; T. M., Kiran Kumar; Sarangi, Khitish Kumar (Frontiers in Sustainable Food Systems, 2023)
The study of Ecosystem Services (ES) has gained currency for two broad reasons. First to quantify the ES that the humans are enjoying; second to incentivize the people or institutions who contribute towards the improvement of ES. Agriculture being a dominate form of land management, acts as both provider and consumer of ES. The present study is an attempt to map the ecosystem services and assess the agricultural ecosystem services at the village landscape in the Eastern India. The study aims to understand the various ES, inter-linkages and the trade-off over time that have affected the welfare of the households in a region of Eastern India. We found that the village being close to the forest area had a diverse ecosystem fostering over 60 ecosystem goods that provided over 200 ecosystem services to the villagers. Moreover, all the four ecosystems, viz., Forest, Water, Grassland and Agricultural Ecosystems of the village along with the human resources were integrated and interdependent on each other. However, over a period of time there had been significant changes in the ES and also in the dependency of the households over the ecological services. Finally, the valuation of agro-ecosystem services (paddy and fallow land ecosystems) was done using benefit transfer method. The value of the ES under rice-ecosystem was estimated at US 61964.57 year-1 whereas US 9667.8 year-1 was under fallow lands resulting in a total of US 71632.37 year-1 worth of total services from agro-ecosystem. We suggest comprehensive research work for designing context-specific tools to identify and measure ES. Further we recommend appropriate policy mix by including synergies and trade-offs among different ES.